Pengaruh Ulasan, Kemudahan, Kepercayaan Konsumen, dan Harga terhadap Keputusan Pembelian di Tokopedia - Juniwati; Abdurrahman (CV Edujavare Publishing, 2023)
This study aims to determine the effect of reviews, convenience, consumer trust and price on purchasing decisions at Tokopedia. The population in this study were users of Tokopedia generation z and millennials in Jakarta. The sampling method used purposive sampling technique, so that a sample of Tokopedia users of generation z and millennials in Jakarta who met the predetermined criteria was obtained as many as 100 respondents. The statistical tool used is associative statistics with data processing using SPSS Statistic 23 software. The results of this study indicate that product reviews have no effect on purchasing decisions at Tokopedia. Ease of use has a positive influence on purchasing decisions at Tokopedia, consumer trust positively affects purchasing decisions at Tokopedia, and price has a positive effect on purchasing decisions at Tokopedia.